Nonlinear coupling and instability of heave, roll and pitch motions of semi-submersibles with bracings. (November 2018) - Wei, Handi; Xiao, Longfei; Tian, Xinliang; Low, Ying Min
Abstract: Nonlinear coupling is an important safety consideration for offshore floating structures. Traditional mathematical models like linear motion equations are inadequate for predicting the nonlinear resonance of semi-submersible platforms with bracings. In this study, we proposed a mathematical model that considers the nonlinear effects of heave motion on pitch restoring coefficient, pitch motion on buoyancy, and bracings on buoyancy. Regular wave tests and numerical simulations were performed to investigate the characteristics of coupled motions and to validate the proposed mathematical model. Under head, quartering and beam sea conditions, motion instability of the semi-submersible platform occurred when the incident wave period approached the natural period of heave. In addition, a double-period phenomenon and unique pitch-motion profile were observed. Good agreements between experimental and nonlinear numerical results validated the ability of the proposed mathematical model to accurately simulate nonlinear effects and predict motion instability. Using the validated model, factors affecting the motion instability were analysed and measures to minimize instability were recommended.